Daily mean stream temperatures in Central Spain - José María Santiago; Carlos Alonso; Diego Garcia de Jalón (PANGAEA, 2017)
In total, 21 sites in 9 mountain rivers in the centre of Spain (between the latitudes of 40°18 extquotesingle and 41°21 extquotesingle N). Sites are located in the Tormes River and its tributaries, the Barbellido River, the Gredos Gorge and the Aravalle River (in the Duero Basin); the Cega River and the Pirón River (the Pirón River is a tributary of the Cega River in the larger Duero Basin); the Tagus River, the Gallo River, and the Cabrillas River (all four of which are in the Tagus Basin). At each study site, water temperatures were recorded every 2 h throughout the year using 31 Hobo Water Temperature Pro v2 (Onset) and Vemco® Minilog data loggers. Loggers were tested for malfunctions before being deployed and were placed at bottom of the streams avoiding direct solar radiation . Depth -these are shallow streams- and position in the stream section were not relevant as it was verified.
Supplement to: Santiago, José María; Muñoz-Mas, Rafael; Solana-Gutiérrez, Joaquín; Garcia de Jalón, Diego; Alonso, Carlos; Martínez-Capel, Francisco; Pórtoles, Javier; Monjo, Robert; Ribalaygua, Jaime (2017): Waning habitats due to climate change: the effects of changes in streamflow and temperature at the rear edge of the distribution of a cold-water fish. Hydrology and Earth System Sciences, 21(8), 4073-4101, https://doi.org/10.5194/hess-21-4073-2017